2018
DOI: 10.1016/j.cyto.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory profile analysis reveals differences in cytokine expression between smokers, moist snuff users, and dual users compared to non-tobacco consumers

Abstract: We identified a set of five proteins as potential biomarkers that can inform of inflammation status due to tobacco usage. Our findings contribute a better understanding of how the use of different tobacco products contributes to inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“… 13 , 14 In fact, a recent study suggested serum fibrinogen as a marker to differentiate ST users from tobacco smokers, as smokers were found to have elevated fibrinogen levels, while the serum fibrinogen was similar in ST users and non-tobacco users. 15 The present study showed raised serum fibrinogen and d-dimer levels among oral tobacco users as compared to non-tobacco users. This finding reiterates the variability in the systemic response across the spectrum of ST products.…”
Section: Discussionsupporting
confidence: 49%
“… 13 , 14 In fact, a recent study suggested serum fibrinogen as a marker to differentiate ST users from tobacco smokers, as smokers were found to have elevated fibrinogen levels, while the serum fibrinogen was similar in ST users and non-tobacco users. 15 The present study showed raised serum fibrinogen and d-dimer levels among oral tobacco users as compared to non-tobacco users. This finding reiterates the variability in the systemic response across the spectrum of ST products.…”
Section: Discussionsupporting
confidence: 49%
“…The effects of cigarette smoking (CS) on human health have been extensively investigated at the organ, cellular, and molecular levels. Cigarette smoking has been linked to perturbations in many molecular pathways, including oxidative stress and immune response [ 4 ]. Several toxins present in CS have immunomodulatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…These results may be influenced by heterogeneous sampling methods, laboratory processing methods and data analysis 15 . An additional complicating factor is that clinical comorbidities which are strongly associated with disease activity in HS, such as obesity 16 , diabetes 17 , inflammatory bowel disease 18 , and smoking 19 also impact inflammatory cell activity in the skin 18,[20][21][22] . Hence it remains unclear whether the presence or absence of these conditions may confound the findings of immunohistochemical studies in HS 15,23 and whether clinical stratification of patients is required to identify distinct pathogenic pathways, which may be amenable to pharmacological intervention.…”
Section: Introductionmentioning
confidence: 99%